Yoga as a Preventive Intervention for Cardiovascular Diseases and Associated Comorbidities: Open-Label Single Arm Study - Sharma, Kaushal; Basu-Ray, Indranill; Sayal, Natasha; Vora, Ariana; Bammidi, Sridhar; Tyagi, Rahul; Modgil, Shweta; Bali, Parul; Kaur, Paramvir; Goyal, Atul Kumar; Pal, Deepak Kumar; Arvind, Harshita; et al. (Frontiers in Public Health, 2022)
Aim Common Yoga Protocol (CYP) is a standardized yoga protocol authored by experts from all over the world under the aegis of the Ministry of AYUSH, Ayurveda, Yoga and Naturopathy, Unani, Siddha, Sowa Rigpa and Homeopathy (AYUSH). The potential of CYP can be determined as a cost-effective lifestyle modification to prevent the risk of developing cardiovascular diseases (CVD). Methods In this prospective trial, we compared the effect of CYP at baseline and after 1 month. A total of 374 yoga-naïve participants performed CYP under the supervision of experienced trainers. Physiological [body mass index (BMI), blood pressure, percent oxygen saturation], biochemical (fasting blood glucose and lipid profile), and neurocognitive parameters were measured before and after the intervention. Results At day 30 of yoga practice, serum levels of low-density lipoprotein (LDL), total cholesterol (TC), and high-density lipoprotein (HDL) were found significantly improved as compared to the baseline levels observed at the time of enrollment. Similarly, the lipid profile was also obtained from experienced trainers and found to be significantly different from those of yoga-naïve volunteers. When the intervention was compared between the healthy yoga-naïve participants with yoga-naïve participants suffering from medical issues, it was found that cholesterol profile improved significantly in the healthy-naive group as compared to the diseased group (hypertension, diabetes, underwent surgery, and CVD). Conclusion These results highlight the need for further research to better understand the effects of yoga on the primary prevention of CVD.